Translation Techniques and Errors in a Folktale: A Comparison between Students and Alumnae - Muhammad Zaid Muttaqin; Issy Yuliasri (Language Circle: Journal of Language and Literature, 2025)
This study compares translation techniques and errors found in the Indonesian translations of an English folktale by two distinct groups: current students and alumnae of the English Education Department. Drawing on Molina and Albir’s taxonomy of translation techniques and the error classification by the National Accreditation Authority for Translators and Interpreters (NAATI), the research employs a qualitative descriptive design. Participants, ten students and ten alumnae selected via purposive sampling, translated the folktale The Stonecutter. Their translations were analyzed to identify patterns in technique use and error frequency. The findings highlight the impact of experience and training on translation quality, offering implications for translation pedagogy.